EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN JAGUNG (Zea mays L.) BERDASARKAN ZONA AGROEKOLOGI PADA SKALA 1:50.000 DI KABUPATEN LEBAK - Firnia, Dewi; Hermita, Nuniek; Nurjaman, Sofiyan Aditiya (Jurnal Agroekoteknologi, 2015)
Corn corp (Zea mays L.) is the second commodity food after rice. Corn crop is a plant that in its growth and development process need environmental factor, such as land. Land factor has big contribution in supporting growth and development of plants. Therefore, land has to be evaluated as of the commodities that will be cultivated can provide optimal results. The purpose of this research was to assess land suitability classes and provide direction zoning commodity corn crops in Lebak regency and provide alternative improvement of the limiting factors in an effort to increase corn production. Descriptive method based on desk study activities and survey was used in this research. Principal of that method was based on approach of landscape mapping and the interpretation of aerial photographs or satellite images, then land evaluation of that land units. Agro-ecological zones parted as 5 zones and 18 sub zones. Zones that being in research areas were zone I (forestry), II (annual plants/plantation), III (annual plants and crops), IV (crops) and VII (forestry/pasture). Based on its land suitability for corn crops were in agro-ecological zone III and IV. In research area agro-ecological zone III and IV that suitable for corn commodities planting were 7 sub zones, there were III/Df;h;ei (S2-tc/wa/rc), III/Dhf;sp (S2-tc/wa/rc), IV/Df;h;ei (S2-tc/rc), IV/Dfs,hv/Wr (S2-tc/rc), IV/Dhf/Wr (S2-tc/rc), IV/Dfe/Wr (S2-tc), and IV/Wr/Dhf (S2-tc/rc), with land area reaches 62.877 ha or about 18,92% from the total of Lebak regency land area is 332.371 ha.